FACTORS RELATED TO EYE FATIGUE IN CUSTOMER SERVICE EMPLOYEES 2022 - Putri Gunawan, Arni; Cempaka Putri, Eka; Millah, Izzatu; Handayani, Rini (Journal of Vocational Health Studies, 2023)
Background: Eye fatigue is a symptom caused by excessive efforts of the visual system, which is in less than perfect condition to obtain visual acuity. This is influenced by gender, duration, and distance of viewing the monitor. Purpose: Analyze the factors and images related to eye fatigue in customer service employees at PT X in 2021. Method: Descriptive study with cross-sectional design with the total sampling method. The sample in this study was 50 people. The population in this study was 50. This research was conducted on December 27 – January 5, 2022. Data collection was obtained by collecting primary data and secondary data. Data were analyzed by univariate and bivariate using the Chi-square test. Result: That the highest proportion is found in employees who experience eye fatigue complaints as many as 44 people (88%), in employees aged â‰¤40 years as many as 42 people (84%), employees who have female sex as many as 32 people (64% ), employees who have a working period of >3 years as many as 45 people (90%), had computer use >8 hours a day as many as 46 people (92%), saw a monitor distance of 50 cm as many as 38 people (76%), and there was a relationship between gender (p-value = 0.001), duration of computer use (p-value = 0.004), monitor viewing distance (p-value = 0.002) with the incidence of eye fatigue in customer service employees at PT X in 2022. Conclusion: The results show that eye fatigue does not get worse by placing the computer in such a way that there is no light reflection, conducting periodic medical check-up, and educating employees to intersperse computer use time.